“It’s been like a spiritual awakening for me”: the impacts of traumatic brain injury education with Aboriginal and Torres Strait Islander women in the Australian correctional system - Michelle S. Fitts; Michelle S. Fitts; Michelle S. Fitts; Michelle S. Fitts; Jennifer Cullen; Jennifer Cullen; Jennifer Cullen; Rachel Montgomery; Rachel Montgomery; Aunty Glenda Duffy; Aunty Glenda Duffy (Frontiers in Education)
IntroductionA majority of Aboriginal and Torres Strait Islander women in correctional centers report prior experience of traumatic brain injury (TBI) from assault. TBI education in settings outside correctional centers, such as health settings, is shown to help people living with TBI implement strategies for symptom management. The aim of this study was to understand and identify what impacts TBI education would have for Aboriginal and Torres Strait Islander women in correctional centers in Australia.MethodsIn August 2023, two Aboriginal facilitators from a national brain injury organization delivered workshops on brain injury, with a primary focus on TBI, to 15 women involved in a peer-mentor support group (Sisters for Change) at one regional correctional center in Queensland (Australia). TBI resource packages were also shared with Aboriginal and Torres Strait Islander women at the correctional center with lived experience of TBI from family violence. Nine semi-structured interviews were conducted with Aboriginal and Torres Strait Islander women who attended the workshops and/or received the TBI information resource packages. Thematic analysis was conducted on interview transcripts as well as the written notes recorded from the workshops.ResultsThe workshops supported women to develop a deeper understanding of brain anatomy, impacts of physical violence on brain function and how TBI appears in everyday life, both inside a correctional center and in the community. Aboriginal and Torres Strait Islander women reported gaining deeper insight into, and greater compassion for, themselves and other women at the correctional center who have histories of family violence.ConclusionThe findings underscore the need for greater consideration of how TBI education and screening pathways can contribute to the provision of appropriate and responsive supports for Aboriginal and Torres Strait Islander women in correctional centers and subsequent to their release from the correctional center.